2009
DOI: 10.1007/s10791-008-9086-4
|View full text |Cite
|
Sign up to set email alerts
|

A user-centric approach to identifying best deployment strategies for language tools: the impact of content and access language on Web user behaviour and attitudes

Abstract: The number of Web users whose first language is not English continues to grow, as does the amount of content provided in languages other than English. This poses new challenges for actors on the Web, such as in which language(s) content should be offered, how search tools should deal with mono-and multilingual content, and how users can make the best use of navigation and search options, suited to their individual linguistic skills. How should these challenges be dealt with? Technological approaches to nonEngl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…They also noted this facility had language selection, although no participant used an alternative language to English. This is found to confirm the notion that lower cognitive effort of the search option (in this case the wizard) can directly affect the preference of said search option [2]. It also highlights the point regarding the language of the in-site links' diminishing the multilinguality of the web.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…They also noted this facility had language selection, although no participant used an alternative language to English. This is found to confirm the notion that lower cognitive effort of the search option (in this case the wizard) can directly affect the preference of said search option [2]. It also highlights the point regarding the language of the in-site links' diminishing the multilinguality of the web.…”
Section: Resultssupporting
confidence: 71%
“…A number of studies have looked at multilingual IR, with a rising number of studies investigating the information seeking behaviour of users in relation to language proficiency, notably when English is the foreign language [2,3,13]. Research by [2] focused on web content (or lack thereof) in the user's native language and the impact it had on user satisfaction through cognitive load.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has highlighted a digital divide online due to language barriers (Paolillo, 2005;Kralisch, 2005;Kralisch & Mandl, 2006;Flammia & Saunders, 2007;Berendt & Kralisch, 2009). An overarching theme throughout the past work has been a language bias towards English and this has been reflected in the analysis carried out.…”
Section: People Languages and The Internetmentioning
confidence: 99%
“…Despite the fact that recent figures suggest that only slightly over a quarter of all Internet users are English native speakers [21], relatively little research effort is put into improving the quality of non-English web search [15]. Research has found that, despite the increasing number of users who speak English as a second language (ESL), or do not speak English at all, the extent and quality of content in other languages often does not meet the needs of said users [3]. In addition to this, even when there is sufficient content available, there are a considerable number of mostly unresolved complexities and issues of monolingual search in non-English languages [15,22].…”
Section: Introductionmentioning
confidence: 99%